(untitled) (Research, Society and Development, 2022)
Guillain-Barré Syndrome (GBS), also known as acute polyradiculoneuritis, is the largest cause of generalized flaccid paralysis in the world. due to reversible manifestations, however, in 20% of cases, it can leave sequelae in the patient, such as changes in muscle tone and loss of strength, which make it difficult to perform activities of daily living, in normal situations, most cases occur sporadically. and does not seem to show seasonality, it is an autoimmune disease that primarily affects the myelin of the proximal portion of peripheral nerves in an acute/subacute way, in most cases patients usually present signs and symptoms such as blurred vision, tachycardia, dysphagia, dizziness, urinary incontinence and damage to the respiratory part and also presenting a lot of weakness more in the proximal muscles and lower limbs res are generally more affected than the upper limbs. Physiotherapy has as main objective at all stages of the disease to prevent comorbidities, improve balance, recover muscle strength and improve physical conditioning, the physiotherapeutic conduct will be established according to the needs of each patient and the phase in which it is finds, always seeking to reduce their deficits for the return of ADL’s and improve the quality of life.